Toll‐like receptors 2, 4, and 9 in primary, metastasized, and recurrent oral tongue squamous cell carcinomas. (1st October 2015) - Mäkinen, Laura K.; Ahmed, Abdirisak; Hagström, Jaana; Lehtonen, Sanna; Mäkitie, Antti A.; Salo, Tuula; Haglund, Caj; Atula, Timo
Abstract : Background: Toll‐like receptors (TLRs) are pattern‐recognizing proteins involved in innate immunity and they seem to regulate both cancer progression and inhibition. In oral cancer, TLR activation has been linked to invasion. To define the role of TLR‐2, TLR‐4, and TLR‐9 in oral tongue squamous cell carcinoma (OTSCC), we studied their expression in vivo in OTSCC tumor samples, as well as in vitro in cell invasion model. Methods: We used immunohistochemistry to compare the expression of TLR‐2, TLR‐4, and TLR‐9 in 21 primary Stage I‐II OTSCCs, neck metastases, and recurrent tumors. In addition, we used myoma organotypic invasion assay to evaluate the effect of GIT27 (4, 5‐dihydro‐3‐phenyl‐5‐isoxasoleaceticacid) on the invasion of the HSC‐3 OTSCC cell line. Results: TLR‐2, TLR‐4, and TLR‐9 were expressed in most tumors. Nuclear TLR‐2 expression occurred more often in primary tumors than in neck metastases or recurrent tumors of the neck, whereas nuclear TLR‐4 expression and cytoplasmic TLR‐9 expression were higher in primary tumors than in local recurrent tumors. GIT27 did not affect the invasion of HSC‐3 OTSCC cells, but a myoma organotypic invasion assay revealed that the expression of TLR‐2 and TLR‐4 was stronger in deeper‐invading cells. Conclusions: TLR‐2, TLR‐4, and TLR‐9 were expressed in primary tumors, neck metastases as well as in recurrent tumors of OTSCC. Thus, these receptors seem to play a role in both the development and progression of tongue carcinoma. These TLRs may also contribute to the invasive potential of OTSCC.